2002
DOI: 10.1001/archopht.120.11.1517
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Frontal Air Bags on Eye Injury Patterns in Automobile Crashes

Abstract: To investigate eye injuries resulting from frontal automobile crashes and to determine the effects of frontal air bags. Methods:The National Automotive Sampling System database files from January 1, 1993, through December 31, 1999, were examined in a 3-part study that included an investigation of 22 236 individual crashes that occurred in the United States. A new 4-level eye injury severity scale that quantifies injuries based on recovery time, need for surgery, and possible loss of sight was developed.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 79 publications
2
28
0
Order By: Relevance
“…Not all casualties had AIS codes assigned, so ICD-9 codes were adapted to the injury scale (Table 1). 14 Although there is another injury scoring system, Ocular Trauma Score, this system was not used because of the way eye injuries were documented in the JTTR. 15 Laceration of the eye, unspecified 871.…”
Section: Methodsmentioning
confidence: 99%
“…Not all casualties had AIS codes assigned, so ICD-9 codes were adapted to the injury scale (Table 1). 14 Although there is another injury scoring system, Ocular Trauma Score, this system was not used because of the way eye injuries were documented in the JTTR. 15 Laceration of the eye, unspecified 871.…”
Section: Methodsmentioning
confidence: 99%
“…The number of occupants sustaining injuries greatly exceeds fatalities in magnitude as 931,000 are injured in frontal collisions. 47 Injuries sustained in motor vehicle collisions range from extremity [20][21][22]28,29,39,42 and eye [23][24][25]27 injuries, to more serious head 17 and chest 26,34,40,41 injuries. The total economic cost incurred as a result of motor vehicle collisions in 2000 totaled $230.6 billion.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, approximately 66,000 people suffered from vehicle-related eye injuries in the United States (Mcgwin et al, 2005). Of the vehicle occupants sustaining an eye injury during a crash, as many as 15-25% sustain severe eye injuries (Duma and Crandall, 2000;Duma et al, 2002) and it was shown that within these severe eye injuries as many as 45% resulted in globe rupture (Kuhn et al, 1994).…”
Section: Introductionmentioning
confidence: 99%